The role of teachers in guiding student peer interactions: conceptions of pre-service teachers - Heinimäki, Olli-Pekka; Kajamies, Anu; Tiilikainen, Mikko; Vauras, Marja (SPRINGER, 2025)
Teachers play a pivotal role in guiding students' peer interactions, yet the nature of this role warrants further investigation. This study addresses this gap by investigating second-year pre-service classroom teachers' conceptions of this role, both before and after a course that integrated theory and practice in interaction and socioemotional skills. The analysis of pre-service teachers' written conceptions revealed a spectrum of roles, which were then clustered into broader role profiles. Overall, roles pertaining to organization and management, as well as instructional roles, were prioritized over those concerning socioemotional support. However, notable shifts in conceptions were observed over the course, indicating an evolving understanding. The findings suggest that teacher education programs should place greater emphasis on providing pre-service teachers with opportunities to reflect on, experiment with, and practice a variety of teacher roles-ultimately expanding their role repertoire and strengthening their ability to flexibly adapt their roles to the needs of interacting students.